THE INFLUENCE OF PRICE PERCEPTIONS, DIGITAL PROMOTIONS, AND SERVICE QUALITY ON SALES LEVELS OF SOUTH WHEEL BUILDING MATERIALS AT TOKOPEDIA - Nika Ponika Purnama Dewi; Suadi Sapta Putra; Kumba Digdowiseiso (SEAN Institute, 2023)
The aim of this research is to analyze the influence of price perceptions, digital promotions, and service quality on sales levels of Roda Selatan building materials on Tokopedia. The population of this research is customers of Roda Selatan building materials on Tokopedia. Sampling was carried out by purposive sampling consisting of 100 respondents. The technique used is inferential analysis with multiple linear regression and using the Statistical Product and Service Solution (SPSS) version 25.0 program. The results of multiple linear regression analysis show that the Price Perception variable (X1) has an influence of 0.395 or 39.5%, the Digital Promotion variable (X2) has an influence of 0.287 or 28.7%, and the Service Quality variable (X3) has an influence of 0.315 or 31.5% on Sales Level. Thus, it can be concluded that the variables of price perception, digital promotion, and service quality influence sales levels together.